APPLICATION OF GROUP INVESTIGATION (GI) COOPERATIVE LEARNING MODEL TOWARDS STUDENTS` PROBLEM SOLVING SKILLS ON ENVIRONMENTAL POLLUTION CONCEPTS - nesia premurdia; Tri Jalmo; rini rita marpaung (Universitas Lampung, 2013)
This study aims to find out the improvement of students` problem solving skills on environmental pollution and conservation concepts of X grade student of SMA N 1 Talang Padang using Group Investigation learning model. The study used pretest-posttest non equivalent design. Sample were X5 as experimental class and X3 as control chosen from population using randomized block sampling technique. Data of students problem solving skill was obtained using pretest and posttest, while data of students` learning activities was observed and the data obtained was statistically analyzed using t-test with SPSS 17 program.The study showed that there was improvement of students` problem solving skills with 61.67 N-gain score. The GI learning model effected students` problem solving significantly espescially on three aspects such as identifying problem, formulating problem, and giving alternative solution.The GI learning model also affected students` learning activities significantly on the students expressing opinions / ideas skill and discussions. The study concluded that the GI learning models can improve students' problem solving skills and enhance student learning activities on environmental pollution and conservation concepts.Key words: Group Investigation (GI) learning model, problem solving skills, learning activities, environmental pollution, environmental conservation.